LEGAL PROTECTION FOR LOSS OF MOTORBIKES IN THE PARKING LOT OF THE TOURISM CENTER OF CIREBON REGENCY BASED ON REGIONAL REGULATION NO.11 OF 2019 CONCERNING THE IMPLEMENTATION OF PARKING: (Case study in Bukit Cinta – Mundu, Cirebon Regency) - Andita Alfarisy, Panji; Marlina, Tina; Maulida, Irma (Hukum Responsif, 2024)
Chapter 18, paragraph (1) of the Consumer Protection Law is included and regulated regarding the provisions for the Inclusion of Standard Clauses, where "Business actors in offering goods and or services intended for trading are prohibited from making or incorporating standard clauses on every document and or agreement when stating the transfer of responsibility of business actors", Chapter 18 paragraph (2) of the Consumer Protection Law states that "Business actors are prohibited from including standard clauses whose disclosure is difficult to understand". Chapter 32 of Cirebon Regency Regional Regulation No. 11 of 2019 which states that "Getting a sense of security for the use of Parking Space Units (SRP)". This type of research is Normative Law, which analyzes laws, regulations, and other legal materials. The problem in this study is how to provide legal protection for consumers who lose their motorbikes in the parking lot of the Bukit Cinta Tourism Center, Cirebon Regency and how to resolve disputes in the event of losses on the part of consumers who are parked in the parking lot of the Bukit Cinta Tourism Center, Cirebon Regency.Legal protection for consumers in the parking of motor vehicle tourism objects in Cirebon does not yet exist because of the standard clause on ticket parking related to the transfer of responsibility for the parking manager. This is clearly contrary to Chapter 18, paragraph (1) of the Consumer Protection Law. Including a standard clause with the transfer of responsibility has violated the freedom of contract in the Civil Code. Efforts to resolve disputes if there is a loss to the owner of the vehicle parked at the tourist attraction, then to divide or transfer the burden of responsibility, the parking manager can collaborate with the insurance company to provide parking insurance for each consumer. To protect consumers legally, several options of legal remedies can be pursued by litigation or non-litigation, such as mediation, mediation at the Directorate of Consumer Protection, the Dispute Resolution Agency (BPSK), and the District Court